Penerapan Sistem Informasi Akuntansi Dalam Pengelolaan Keuangan Di Dinas Pendidikan Kota Blitar - Septa Amanda; Irfan Fatoni; Dwi Anggarani (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This research is titled "The Implementation of Accounting Information Systems in Financial Management at the Blitar City Education Office" and aims to examine how Accounting Information Systems (AIS) are applied in financial management within that institution. Using a qualitative descriptive approach, the study involves interviews, observations, and document analysis to gather data. The findings reveal that the implementation of AIS has enhanced efficiency and transparency in recording and reporting financial activities. Furthermore, AIS facilitates faster and more accurate decision-making through the provision of integrated and real-time data. However, the research also identifies challenges such as limitations in human resource competencies and technical issues in system usage. Therefore, ongoing training and infrastructure improvements are necessary to optimize AIS implementation. Overall, this study offers recommendations to improve educational financial management in Blitar City through better utilization of information technology.